Rare Incidence of Umbilical Pseudocyst in a Calf - Bhathra, Nagarajakumar Revathy; Gupta, Chhavi; Akambaram, Sabarinathan; Vaiyapuri, Prabaharan; Ajevar , Ganesan (The Indian Journal of Animal Reproduction, 2025)
Umbilical diseases are one of the most prevalent postpar tum conditions in neonatal calves. The most common umbilical diseases noticed among newborn calves are omphalophlebitis, umbilical hernia, umbilical subcuta neous infection/abscesses, umbilical remnant infections, umbilical abscess (chronic omphalitis) and urachal cysts/ ruptures (Gordan, 2020). Umbilical pseudocyst is a rare congenital umbilical disease of prenatal calf characterized by cystic degeneration or localized oedema of the Wharton jelly which may predispose to omphalocele, haemangio mas and patent urachus (Kaushal et al., 2018).